Development of E-Modules Building Drawings with Autocad for Construction and Property Business Department Students of SMK N 1 Blora - Alfian, Muhammad Habib; Qudus, Nur; Endroyo, Bambang (Journal of Vocational and Career Education, 2021)
Vocational High School (SMK) is one part of the national education system with a strategic role to educate the nation's life. Students are an essential pillar of the nation's next generation, so they must increase their creativity in the learning process to hone their abilities and produce outputs or graduates ready to face challenges in the 21st Century. Choosing the right learning media can improve learning outcomes significantly between those given treatments to students of class XI BKP 3 and those who are not given treatment to students of class XI BKP 1 in SMK Negeri 1 Blora school year 2020/2021. This research aims to develop an E-module for Building Drawing Materials with AutoCAD Applications based on files Electronic Publication (EPUB) to improve student learning outcomes. This study uses research and development methods or R D. The design chosen is ADDIE, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The research uses various instruments, namely (1) a feasibility assessment sheet for e-modules; (2) an e-module practicality questionnaire; and (3) a questionnaire on the effectiveness of the e-module to measure student learning outcomes in class XI BKP 3 and XI BKP 1 at SMK Negeri 1 Blora. The data analysis used is (1) definite to determine the feasibility level of the e-module; (2) Guttman's categorization to determine the level of practicality of e-modules, using the coefficients Kr and Ks; and (3) N-Gain and different N-Gain tests using t-test, to determine the effectiveness of the e-module on student learning outcomes. Based on the feasibility test of the Building Drawing e-module with AutoCAD file-based Electronic Publication (EPUB) developed, according to the responses of media experts and material experts obtained, the e-module response criteria is very feasible. Responses from teachers and students as user responses to the practicality test of the e-module got very applicable assessment criteria. And from the effectiveness test in the experimental class, the e-module received influential and significant standards for improving student learning outcomes in the cognitive and psychomotor aspects. In contrast, in learning outcomes in the affective part, the e-module was not adequate for enhancing student learning outcomes in class XI BKP in SMK N1 Blora.